Hubungan Penggunaan Media Wayang Kertas Terhadap Motivasi Belajar Siswa pada Mata Pelajaran IPS di Kelas 4 MIS Al-Imam Klumpang TA. 2022/2023 - Muliati, Astri; Herdyana, Thessa; Ramadhan, Nuri (Medan Resource Center, 2024)
This study aims to determine the relationship between the use of wayang (paper puppet) media and students' learning motivation in social studies subjects among fourth-grade students at MIS Al-Imam Klumpang during the 2022/2023 academic year. The research adopts a quantitative approach with a descriptive analytical method as outlined by Suryabrata (2013). The study involved 25 students, consisting of 8 males and 17 females. The independent variable in this study is the use of wayang media, while the dependent variable is students' learning motivation. The research was conducted in one action cycle with three meetings: the first for planning, the second for implementation and observation, and the third for reflection. Data were collected using observation, questionnaires, and documentation. Data analysis was performed using the Pearson product-moment correlation test. The results indicate a significance value of 0.068, which exceeds the 0.05 threshold, signifying that there is no statistically significant relationship between the use of wayang media and students' learning motivation. These findings suggest that while wayang media can be an engaging tool, further research is needed to explore its effectiveness in different contexts and with alternative methodologies.